Thermal Remote Sensing for Global Volcano Monitoring: Experiences From the MIROVA System - Coppola, Diego; Laiolo, Marco; Cigolini, Corrado; Massimetti, Francesco; Delle Donne, Dario; Ripepe, Maurizio; Arias, Hidran; Barsotti, Sara; Parra, Claudia Bucarey; Centeno, Riky Gustavo; Cevuard, Sandrine; Chigna, Gustavo; et al. (Frontiers in Earth Science, 2020)
MIROVA (Middle Infrared Observation of Volcanic Activity) is an automatic volcano hot spot detection system, based on the analysis of MODIS data (Moderate Resolution Imaging Spectroradiometer). The system is able to detect, locate and quantify thermal anomalies in near real-time, by providing, on a dedicated website (www.mirovaweb.it), infrared images and thermal flux time-series on over 200 volcanoes worldwide. Thanks to its simple interface and intuitive representation of the data, MIROVA is currently used by several volcano observatories for daily monitoring activities and reporting. In this paper, we present the architecture of the system and its use for operational volcano monitoring and research. Particular emphasis will be given to the contribution that the thermal data has provided in order to detect volcanic unrest, to forecast eruptions and to depict trends and patterns during eruptive crisis. The current limits and requirements to improve the quality of the data, their distribution and interpretation are also discussed, in the light of the experience gained in recent years within the volcanological community. The results presented clearly demonstrate how the open access of satellite data and the sharing of derived products allow a better understanding of ongoing volcanic phenomena, and therefore constitute an essential requirement for the assessment of volcanic hazards.